A reclamação no novo Código de Processo Civil: um desafio entre a segurança jurídica e o poder criativo do julgador - Moraes, José Magno Linhares (2015)
This thesis aims to study the legal institute of Reclamação in two aspects, which should be seen as complimentary to obtain adequate legal certainty to a complex, pluralist and mutant society, namely, as a guarantee instrument of the authority of court decisons and their respective powers, and, on the other hand, as a legal means of promoting the necessary adjustments of paradigma decision to the case. For this purpose, the study of specialized doctrine, case law of our higher courts and the new civil procedure law was fundamental (Law n. 13.105 of 16 March 2015). Since the recognition of reclamação by the Supremo Tribunal Federal case law, as appropriate legal means to ensure the authority of its decisions, based on the theory of implied powers, it became clear that this institute, genuinely Brazilian, would have great utility in our country, deeply marked by cultural and economic contrasts. Court decisions, as legal rules, may give rise to plurality and interpretive inconsistencies. However, in the Democratic Rule of Law, legal certainty is a value of utmost importance. This certainty, in turn, should allow progress on a social reality that suffers daily influx of economic and political events. Therefore, the analysis of legal certainty in the light of systems theory. Also, it is important to highlight the impacts of the discipline of reclamação in the Brazilian legal system. With the possibility of all the country s courts settle legal arguments with binding power through procedural issues, the assumption of jurisdiction and resolution of repetitive demands, reclamação begins to have far-reaching. This new scenario approaches, in a way, our legal system to the world of the stare decisis theory of common law by privileging, now, respect for the determining reasons for the decision. Thus, through reclamação opens a new path to the desired stability, coherence and equality of law and adjudication